Pattern of Biogas Production and Removal of Chemical Oxygen Demand in Semi Continues Hybrid Anaerobic Reactor - Oktavitri, Nur Indradewi; Soegianto, Agoes; Rahman, T.; Saadah, Bidayatus; Trianingtyas, Deavy (IPTEK Journal of Proceedings Series, 2014)
Anaerobic process had been used for treated highly organic substances, such as canteen wastewaterÂ  which had COD around 5000 mg/L. This research aims to investigate pattern of biogas production and COD removal in semi continue anaerobic process. HRT (Hydraulic Retention Times) were used in this research 1,5 hours. The reactor was contained of four cell coulombs from PVC, with height 1 meter. Gravel as media support in hybrid anaerobic reactor. The height of media support is 50 cm. This reactor operated for 14 days. Parameters had been observed are biogas production and COD.. Biogas production after reactor operated 7 days 0,6594 mL and after reactor operated 14 days is 1,4758 mL. COD removals are 38,89 mg/L after operated 7 days and 42,86 mg/L after operated 14 days. In conclusion, COD removal increased after reactor operated 7 and 14 days. The biogas production increased after 7 and 14 operated days. Increasing of biogas production more drastically than COD removal